2012
DOI: 10.1071/wf10131
|View full text |Cite
|
Sign up to set email alerts
|

Fire frequency analysis in Portugal (1975 - 2005), using Landsat-based burnt area maps

Abstract: Abstract. Fire frequency in 21 forest planning regions of Portugal during the period 1975-2005 was estimated from historical burnt area maps generated with semi-automatic classification of Landsat Thematic Mapper (TM) satellite imagery. Fire return interval distributions were modelled with the Weibull function and the estimated parameters were used to calculate regional mean, median and modal fire return intervals, as well as regional hazard functions. Arrangement of the available data into three different tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 20 publications
6
90
1
Order By: Relevance
“…Moritz et al (2009) have explored the consequences of using censored or uncensored fire data and concluded that disregarding censored data may cause distortion of the real fire hazard. Recently, Oliveira et al (2011) have also tested this effect for FRI during the 1975-2005 period for the whole Portugal and confirmed that censoring fire data has a predominant effect on FRI. It is likely to be especially important when the database comprises few fire intervals (e.g.…”
Section: Modelling the Fire Return Intervalsmentioning
confidence: 79%
See 4 more Smart Citations
“…Moritz et al (2009) have explored the consequences of using censored or uncensored fire data and concluded that disregarding censored data may cause distortion of the real fire hazard. Recently, Oliveira et al (2011) have also tested this effect for FRI during the 1975-2005 period for the whole Portugal and confirmed that censoring fire data has a predominant effect on FRI. It is likely to be especially important when the database comprises few fire intervals (e.g.…”
Section: Modelling the Fire Return Intervalsmentioning
confidence: 79%
“…Such differences with our study can be explained by the fact that Portugal is the most fire-prone country in Europe whereas burned areas tend to decrease in France since the 1990's. Oliveira et al (2011) found lower age dependency in regions of Portugal with high portions of shrublands, and higher age dependency for extensively forested regions. This difference with our results can result from the fact that areas with shrublands in Portugal are regularly burned then grazed and have small fires.…”
Section: Comparison With Other Mtesmentioning
confidence: 82%
See 3 more Smart Citations